The Influence of Work Environment and Discipline on Performance Through Additional Employee Income (TPP) at the Regional Secretariat of Kendal Regency. - Novita Dwi Anggraheni; Bambang Guritno ; Aurilia Triani Aryaningtyas (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research was conducted at the Regional Secretariat of Kendal Regency, which aims to analyze and explain the effect of the work environment and discipline on additional employee income (TPP), analyze and explain the effect of the work environment, discipline and additional employee income (TPP) on performance and analyze and explain the influence of the work environment and discipline on performance through additional employee income (TPP) .This study used a sample of 137 people. The data collection method uses observation, questionnaires and documentation. Instrument feasibility test using validity test and reliability test. For tehnik data analysis using multiple regression analysis and model test. The results of this studystate that the work environment and discipline affect the additional employee income (TPP), work environment, discipline and additional employee income (TPP) affect performance, and additional employee income (TPP) does not mediate the effect of work environment and discipline on performance.